New points of The 13th National Congress of Women’s Congress 2022 - 2027 - Nguyễn Hoàng Anh; Nguyễn Hải Hoàng (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
The 13th National Congress of Women’s Deputies was successfully held in Hanoi with many new contents, aiming to promote the tradition, solidarity, creativity, actively integration, self-control of women, build Vietnam Women’s Union organization, actively build the Party, and the political system, and protect women’s legitimate rights and interest. In this article, we focus on clarifying the basic new points shown in the Congress.